Mechanical Effect of an Implant Under Denture Base in Implant-Supported Distal Free-End Removable Partial Dentures - Naomichi Murashima; Yoshiyuki Takayama; Toshifumi Nogawa; Atsuro Yokoyama; Kiwamu Sakaguchi (Dentistry Journal)
Background: In recent years, implant-assisted removable partial dentures (IARPDs) have been used clinically. However, the extent to which additional implants reduce the burden of supporting tissues is unclear. The aim of this study was therefore to investigate the influence of implanted IARPDs on stress sharing among supporting tissues, using finite element (FE) analysis. Methods: FE models were constructed based on the computed tomography (CT) of a patient with a unilateral defect of the mandibular premolars and molars and the surface data of an RPD with cuspids as abutments, designed using computer-aided design software. A titanium implant was placed in the area equivalent to the first premolar, second premolar, or first molar (IARPD4, IARPD5, and IARPD6, respectively). FE analysis was performed for laterally symmetrical models, i.e., bilateral distal free-end IARPDs. A vertical load of 200 N was applied to the central fossa of the artificial premolars or molars (L4, L5, or L6). Results: Equivalent stress in the alveolar mucosa and vertical displacement of the denture was smaller, with IARPDs under L5 and L6 loads, compared to RPDs. However, abutment teeth were displaced upward under an L6 load in the IARPD5 model. Conclusions: Within the limitations of this study, the area corresponding to the first molar was recommended as the location for an implant under the denture base of bilateral distal free-end IARPDs. Implants located in the area corresponding to the second premolar may apply non-physiological extrusion force on abutment teeth under the load on the artificial second molar.